The Escherichia coli O111 and Salmonella enterica O35 Gene Clusters: Gene Clusters Encoding the Same Colitose-Containing O Antigen Are Highly Conserved - Wang, Lei (American Society for Microbiology, 2000)
O antigen is part of the lipopolysaccharide present in the outer membrane of gram-negative bacteria. Escherichia coli and Salmonella enterica each have many forms of O antigen, but only three are common to the two species. It has been found that, in general, O-antigen genes are of low GC content. This deviation in GC content from that of typical S. enterica or E. coli genes (51%) is thought to indicate that the O-antigen DNA originated in species other than S. enterica or E. coli and was captured by lateral transfer. The O-antigen structure of Salmonella enterica O35 is identical to that of E. coli O111, commonly found in enteropathogenic E. coli strains. This O antigen, which has been shown to be a virulence factor in E. coli, contains colitose, a 3,6-dideoxyhexose found only rarely in the Enterobacteriaceae. Sequencing of the O35-antigen gene cluster of S. enterica serovar Adelaide revealed the same gene order and flanking genes as in E. coli O111. The divergence between corresponding genes of these two gene clusters at the nucleotide level ranges from 21.8 to 11.7%, within the normal range of divergence between S. enterica and E. coli. We conclude that the ancestor of E. coli and S. enterica had an O antigen identical to the O111 and O35 antigens, respectively, of these species and that the gene cluster encoding it has survived in both species.